PEMANFAATAN LAHAN DALAM PENGELOLAAN TANAMAN HIDROPONIK UNTUK MENINGKATKAN UMKM DI DESA CIDEHENG TENGAH - Gatot Hartoko; Venty Ramadhanty; Rahmawati Dewi; Suratmi Suratmi; Lastiur Situmorang; Jumaedi Jumaedi; Mutiara Aisyah Lubis (Indonesian Collaboration Journal of Community Services, 2021)
Hydroponics is also known as soilless culture or soilless plant cultivation. So, hydroponics can be interpreted as cultivating plants that utilize water and without using soil as a planting medium. The purpose of counseling activities to the community with the theme "Community Empowerment Through The Use of Appropriate Technology and Development of MSMEs in Hydroponic Plant Management in Curug Sweetness Village" is to provide knowledge about land use with hydroponic systems, to provide literacy about business opportunities that hydroponic plants can create. The methods carried out in this extension consist of three, namely the lecture method, the practice method, and the discussion method. From the counseling results, it can be concluded that the community already knows simple practices related to farming with hydroponic systems